Socioeconomic status and sleep duration among a representative, cross-sectional sample of US adults - Sarah Wetzel; Usama Bilal (BMC Public Health)
Abstract Background Sleep is a crucial determinant of physical and mental health outcomes, and insufficient sleep is highly prevalent among United States adults. Although some risk factors of poor sleep have been extensively studied, including substance use, age, health behaviors, and others, the associations between socioeconomic status (SES) and sleep remain inconclusive. There is limited evidence on SES and sleep duration among the US adult population. This study analyzed the relationships between three SES indicators (poverty, education, and food security), and sleep duration. Methods We used responses from the 2017-March 2020 National Health and Nutrition Examination Survey (NHANES). Respondents younger than 25 years old were excluded. Sleep duration was classified using self-reported sleep time and stratified by work vs. non-workdays. SES was operationalized using three indicators: poverty-income ratio, educational attainment, and food security status. We imputed missing data for socioeconomic status and outcome variables using multiple imputation. Weighted Poisson regression models with robust standard errors were used to calculate the crude and adjusted prevalence ratios for insufficient sleep duration (< 7 h of self-reported sleep) on workdays and non-workdays separately by each of the three SES indicators. Results We included a total of 8,457 individuals. In the adjusted model, participants with lower income, educational status, and food security had significantly higher prevalence of insufficient sleep duration on both workdays and non-workdays. For example, low-income individuals (poverty-income ratio < 1) had 1.22 (95% CI 1.04–1.44) and 2.08 (95% CI 1.61–2.67) higher prevalence of insufficient sleep as compared to high income individuals on workday and non-workdays, respectively. In general, we found larger differences by level of SES indicator for the non-workday than for the workday outcome. There were no major differences in gender-stratified analysis. We also found that lower SES was associated with higher prevalence of excessive sleep (≥ 9 h). Conclusion Socioeconomic status indicators are significantly associated with sleep duration in the US adult population. Lower SES correlates with increased prevalence of insufficient sleep duration, which has implications for the overall wellbeing of US adults with lower SES. Targeted interventions and further research are needed to reduce this disparity.